Etablering af et juridisk tekstkorpus - Dyrberg, Gunhild; Faber, Dorrit; Hansen, Steffen Leo; Tournay, Joan (HERMES - Journal of Language and Communication in Business, 1988)
The project involves the collection of a corpus of English-French-Danish legal texts exemplifying different text types and different themes within the subject area of the law of contract. Each language will be represented by 1 million words. The text corpus will be computerized and is intended as the empirical data for various types of linguistic research such as text typology, text linguistics, syntax, semantics, etc.The principles which govern the assembly of the corpus - strict definition and delimitation of the text universe, combination of text type and theme classification - are assumed to ensure representativity of the corpus.The corpus forms part of a major project under the auspices of the Danish Research Council for the Humanities, "Communication in Language for Special Purposes".